Ternary positive electrode material, preparation method thereof and electrochemical device
By doping aluminum elements into the core of the ternary positive electrode material and covering phosphate on the surface, the problem of insufficient structural stability and cycling performance of the material is solved, and higher battery cycle performance and capacity retention are achieved.
Patent Information
- Application Number
- CN202411912061.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
The structural stability of the existing ternary positive electrode materials is poor, resulting in severe battery capacity decay and poor circulation performance under high charging voltage.
By doping aluminum into the core of the ternary positive electrode material and forming a phosphate coating on the core surface, the structural stability and cyclic performance of the material work together.
Aluminum element doping reduces the degree of cation mixing, reduces harmful phase transitions and internal stresses, and the phosphate coating improves interface stability and electrochemical activity, resulting in improved cycling performance and capacity retention of the battery.
Smart Images

Figure CN119674030A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new energy materials, and in particular to a ternary positive electrode material and a preparation method thereof, and an electrochemical device. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their high energy density, long service life and low self-discharge rate. With the rapid development of new energy vehicles, higher requirements are placed on the safety, stability and energy density of lithium-ion batteries.
[0003] As the active material of the positive electrode of lithium-ion batteries, the performance of ternary positive electrode materials greatly affects the final performance of the battery. However, the existing ternary positive electrode materials have poor structural stability. Under high charging voltage, the prepared battery capacity decays severely and the cycle performance is poor. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a ternary positive electrode material.
[0005] The embodiments of the present application also provide a method for preparing the aforementioned ternary positive electrode material, and an electrochemical device using the ternary positive electrode material.
[0006] In a first aspect, an embodiment of the present application provides a ternary positive electrode material, which includes a core and a coating layer located on the surface of the core, wherein the core is doped with aluminum element and the coating layer contains phosphate.
[0007] In some possible embodiments, the ternary cathode material is a single crystal ternary cathode material.
[0008] In some possible embodiments, the mass percentage of aluminum element in the ternary positive electrode material is A, and A satisfies: 0.03wt%≤A≤0.2wt%.
[0009] In some possible embodiments, the mass percentage of the metal element in the phosphate to the ternary positive electrode material is B, and B satisfies: 0.03wt%≤B≤0.2wt%wt%.
[0010] In some possible embodiments, the phosphate includes at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate.
[0011] In a second aspect, the present application provides a method for preparing a ternary positive electrode material, comprising: Mixing a ternary cathode material precursor, a lithium source and an aluminum source to form a mixed material, and sintering the mixed material once to obtain an aluminum-doped core; and The inner core is mixed with phosphate and subjected to secondary sintering to form a coating layer containing phosphate on the surface of the inner core, thereby obtaining the ternary positive electrode material.
[0012] In some possible embodiments, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum chloride and aluminum phosphate; and / or The mass percentage of the aluminum element in the aluminum source to the total mass of the ternary positive electrode material precursor and the lithium source is N, and N satisfies: 0.03wt%≤N≤0.2wt%.
[0013] In some possible embodiments, the mass percentage of the metal element in the phosphate to the core is M, and M satisfies: 0.03wt%≤M≤0.2wt%; and / or The phosphate includes at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate.
[0014] In some possible embodiments, the primary sintering temperature is 800° C. to 1000° C., and the primary sintering time is 6 h to 18 h; and / or The temperature of the secondary sintering is 300° C. to 800° C., and the time of the secondary sintering is 6 h to 18 h.
[0015] In a third aspect, an embodiment of the present application provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned ternary positive electrode material.
[0016] Compared with the prior art, the ternary positive electrode material provided in the embodiment of the present application has an aluminum element doped in the kernel, and the surface coating contains phosphate. Under the synergistic effect of aluminum doping and phosphate coating, the structural stability of the ternary positive electrode material and the cycle performance of the prepared battery are improved. Among them, the aluminum element is doped in the kernel, which can effectively reduce the degree of cation mixing in the ternary positive electrode material, reduce harmful phase changes, thereby reducing the generation of internal stress and microcracks, and is conducive to maintaining the stability of the crystalline layered structure. The ternary positive electrode material with higher structural stability is conducive to reducing the irreversible capacity loss of the prepared battery during the cycle, while suppressing the substantial decrease in discharge voltage and median voltage. In addition, the phosphate is uniformly coated on the surface of the kernel, which can reduce the direct contact between the kernel and the electrolyte, thereby reducing the dissolution of transition metals in the ternary positive electrode material; moreover, the phosphate coating can also improve the interfacial charge transfer efficiency between the ternary positive electrode material and the electrolyte, further improving the structural stability and cycle performance of the ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1A process flow chart of the method for preparing the ternary positive electrode material provided in an embodiment of the present application.
[0018] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.
[0019] Figure 3 This is a scanning electron microscope image of the ternary positive electrode material in Example 1 of the present application.
[0020] Figure 4 This is a scanning electron microscope image of the ternary positive electrode material in Comparative Example 1 of the present application.
[0021] Figure 5 This is a comparison chart of the first charge and discharge capacities of button cells prepared with ternary positive electrode materials in Examples 1-8 of the present application and Comparative Examples 1-2.
[0022] Figure 6 This is a comparison chart of the high temperature cycle performance of button cells prepared with ternary positive electrode materials in Examples 1-8 of the present application and Comparative Examples 1-2. DETAILED DESCRIPTION
[0023] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0024] The inventors of this application have found that the layered structure of the ternary positive electrode material is prone to cation mixing, which will destroy the ordered structure of the ternary positive electrode material, resulting in problems such as capacity loss and decreased cycle performance. At the same time, the ternary positive electrode material will also undergo interfacial side reactions with the electrolyte, causing structural damage and decreased cycle performance. In addition, during the cycle, especially under high voltage charge and discharge, the ternary positive electrode material is prone to phase change, such as from a layered structure to an unstable spinel structure. This phase change easily causes the particle volume to expand or shrink, increasing the internal stress, resulting in more cracks in the particles and structural collapse. These problems jointly lead to a decrease in the structural stability and cycle performance of the ternary positive electrode material.
[0025] To this end, an embodiment of the present application provides a ternary positive electrode material, which includes a core and a coating layer located on the surface of the core, wherein the core is doped with aluminum elements and the coating layer contains phosphate.
[0026] First, aluminum is doped in the core of the ternary cathode material. Since aluminum has strong electron-withdrawing ability and small ionic radius, it can occupy lattice positions together with nickel, cobalt, manganese and other elements. The addition of aluminum can adjust the charge distribution in the core, so that the metal ions are more evenly distributed in the lattice, thereby effectively reducing the degree of cation mixing and reducing harmful phase changes. At the same time, after aluminum doping, the Ni-O bond length is reduced, the bond energy is increased, the dissolution and diffusion of metal ions in the electrolyte are reduced, and the structural stability and capacity of the ternary cathode material are improved. The improvement of the structural stability of the ternary cathode material can reduce the internal stress of the ternary cathode material particles and reduce the generation of particle microcracks, which is conducive to maintaining the integrity and stability of the layered structure. The ternary cathode material with high structural stability is conducive to reducing the irreversible capacity loss of the prepared battery, while suppressing the significant decrease in discharge voltage and median voltage, and improving the battery cycle performance. However, aluminum doping may form impurity phases (LiAlO2 and / or Li5AlO4), which may cause a certain degree of reduction in battery capacity.
[0027] Therefore, the present application further improves the structural stability and cycle performance of the ternary positive electrode material by forming a phosphate-containing coating layer on the surface of the core doped with aluminum: the coating layer reduces the direct contact between the core and the electrolyte, reduces the occurrence of side reactions, thereby improving the interface stability between the surface of the ternary positive electrode material and the electrolyte, and reduces the dissolution of transition metals in the ternary positive electrode material, reducing capacity loss. At the same time, phosphate can also improve the ion migration ability and electron transfer ability of the surface of the ternary positive electrode material, promote charge transfer on the interface, improve the rate performance of the ternary positive electrode material, and further improve the structural stability, cycle performance and thermal stability of the ternary positive electrode material.
[0028] In this application, aluminum doping and phosphate coating work together. Aluminum doping in the lattice inhibits the migration of transition metal ions, reduces volume changes, and thus stabilizes the crystal structure. However, aluminum doping may form impurity phases (LiAlO2 and / or Li5AlO4), which reduces the battery capacity, while phosphate coating can reduce transition metal dissolution and promote the diffusion of lithium ions, thereby improving the capacity and rate performance of the ternary positive electrode material. The two work together to jointly ensure the rate performance and cycle stability of the ternary positive electrode material. Aluminum doping in the core improves the internal crystal stability and internal lithium ion transmission efficiency of the ternary positive electrode material, and phosphate coating on the surface of the core improves the surface structural stability and surface electrochemical activity of the ternary positive electrode material. This internal and external synergistic approach effectively improves the structural stability and cycle performance of the ternary positive electrode material, so that the battery made of the ternary positive electrode material can more efficiently utilize lithium ions during the charge and discharge process, reduce irreversible reactions, and improve the charge and discharge efficiency and capacity retention rate of the battery.
[0029] In some embodiments, the ternary positive electrode material is a single crystal ternary positive electrode material, and the element distribution in the single crystal ternary positive electrode material is more uniform, which makes it more suitable for the doping of aluminum elements, thereby effectively reducing the cation mixing phenomenon and improving the cycle performance and capacity retention rate of the ternary positive electrode material. At the same time, the single crystal structure is also more conducive to the uniform coverage of the surface phosphate and improves the coating effect. In addition, the crystal structure of the single crystal ternary positive electrode material is complete and orderly, without the presence of grain boundaries in polycrystalline materials, and with fewer lattice defects, it also has higher structural stability and high temperature stability.
[0030] In some embodiments, the mass percentage of aluminum in the ternary positive electrode material is A, and A satisfies: 0.03wt%≤A≤0.2wt%. The aluminum element is appropriately doped in the core, which can further improve the structural stability and cycle performance of the ternary positive electrode material without destroying the crystal structure and electrochemical properties (such as capacity and rate performance, etc.) of the material. A can further be 0.05wt%~0.15wt%, and can be 0.03wt%, 0.05wt%, 0.07wt%, 0.1wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt% or any value within the numerical range composed of any two of the above values. When the doped aluminum element is too much (greater than 0.02wt%), it may have a negative impact on the performance of the ternary positive electrode material: first, excessive aluminum doping may cause instability of the crystal structure, cause lattice distortion or form an unstable spinel phase, thereby affecting the overall structural stability of the material. Secondly, although the right amount of aluminum doping helps reduce cation mixing, excessive doping may lead to an increase in residual lithium on the surface of the ternary cathode material, thereby affecting the cycle performance and capacity retention rate of the ternary cathode material. In addition, excessive aluminum doping may also reduce ionic conductivity, thereby affecting the charge and discharge efficiency of the battery. When the amount of doped aluminum is too small (less than 0.03wt%), it may not be able to effectively improve the structural stability and cycle performance of the ternary cathode material.
[0031] In some embodiments, the phosphate contains metal elements, and the mass percentage of the metal elements in the phosphate in the ternary positive electrode material can be B, and B satisfies: 0.03wt%<B≤0.20wt%. The moderate coating of the phosphate can balance the performance improvement of the ternary positive electrode material and the stability of the coating layer. B can further be 0.05wt%~0.1wt%, and can be 0.03wt%, 0.05wt%, 0.07wt%, 0.1wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt% or any value in the numerical range composed of any two of the above values. When the coated phosphate is too much (greater than 0.2wt%), the phosphate coating layer may be too thick, thereby increasing the surface resistance of the ternary positive electrode material, resulting in the diffusion of lithium ions being hindered, thereby reducing the charge and discharge efficiency and rate performance of the battery; it may also hinder the electrochemical reaction of the battery, affecting the power output and rapid charge and discharge capability of the battery; excessive phosphate may also cause the overall specific capacity of the ternary positive electrode material to decrease. When the coated phosphate is too little (less than 0.03wt%), it may be difficult to effectively coat the core, reduce the contact between the core and the electrolyte, and effectively increase the lithium ion transfer rate on the surface of the ternary positive electrode material.
[0032] In some embodiments, the phosphate may include at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate. The above phosphate has good chemical stability and ionic conductivity, and can effectively improve the interface stability, cycle performance, rate performance and stability under high voltage of the ternary cathode material.
[0033] Compared with the prior art, the ternary cathode material provided in the embodiment of the present application has the following beneficial effects: 1. The core is doped with aluminum, thereby reducing the degree of cation mixing in the ternary cathode material and improving the stability of the crystal layered structure. Further controlling the content of aluminum in the ternary cathode material is conducive to balancing the electrochemical performance and structural stability of the ternary cathode material.
[0034] 2. Surface coating with phosphate can effectively improve the chemical stability and conductivity of the surface of the ternary cathode material, thereby improving the interface stability, cycle performance and rate performance of the ternary cathode material. Further controlling the content of phosphate in the ternary cathode material is conducive to balancing the electrochemical performance of the ternary cathode material and the stability of the coating layer.
[0035] 3. The core is doped with aluminum and then coated with phosphate. The two work synergistically to improve the capacity, rate performance and cycle performance of the ternary positive electrode material.
[0036] 4. The ternary cathode material can be single crystal. Compared with polycrystalline materials, it is suitable for doping aluminum in the core and coating phosphate on the surface, which can further improve the doping and coating effects. The atomic arrangement inside the single crystal particles is more orderly, with fewer lattice defects and higher crystal structure stability. Therefore, during long-term charging and discharging, the single crystal ternary cathode material exhibits better cycle performance, lower capacity attenuation and higher high temperature stability.
[0037] Based on the same inventive concept, please refer to Figure 1 As shown, the present embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps: Step S1, mixing a ternary positive electrode material precursor, a lithium source and an aluminum source to form a mixed material, and sintering the mixed material once to obtain an aluminum-doped core.
[0038] Among them, aluminum can occupy the core lattice position together with nickel, cobalt, manganese and other elements. The addition of aluminum can adjust the charge distribution in the core, making the metal ions more evenly distributed in the lattice, thereby effectively reducing the degree of cation mixing, reducing harmful phase changes, and improving structural stability. It is also beneficial to reduce the internal stress of the core, reduce the generation of microcracks, maintain the integrity of the layered structure, thereby reducing irreversible capacity loss and improving cycle performance.
[0039] The core can be a single crystal structure, which is conducive to the doping of aluminum elements and subsequent phosphate coating. The single crystal core has good crystal integrity and excellent mechanical properties, which can effectively reduce the stress concentration and crack formation caused by the grain boundary, reduce the damage and capacity decay caused by stress during the cycle, and extend the service life. In addition, the elements in the single crystal structure are arranged more orderly, which can effectively reduce the cation mixing phenomenon and improve the electrochemical stability compared to polycrystalline materials.
[0040] In some embodiments, the primary sintering temperature is 800°C to 1000°C. A higher primary sintering temperature can promote grain growth, reduce the number of grain boundaries and grain boundary defects, and is conducive to forming a single crystal core with good dispersion, and is conducive to the doping of aluminum into the single crystal core and uniform dispersion. The primary sintering temperature can further be 900°C to 1000°C, and can be 800°C, 900°C, 915°C, 930°C, 935°C, 950°C, 975°C, 1000°C or any value within the range of any two of the above values.
[0041] In some embodiments, the time of a sintering may be 6 hours to 18 hours, which is conducive to sufficient sintering to form the inner core. The time of a sintering may further be 12 hours to 16 hours, and may be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, or any value within the range of any two of the above values.
[0042] In some embodiments, the primary sintering atmosphere may be air atmosphere, oxygen-rich atmosphere or pure oxygen atmosphere, which is conducive to maintaining the metal ions in the core in an oxidized state. The primary sintering atmosphere may further be oxygen-rich atmosphere or pure oxygen atmosphere, which is conducive to forming a stable single crystal structure.
[0043] In some embodiments, the aluminum source may include at least one of aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum chloride, aluminum sulfate, and aluminum phosphate, and the aluminum element is introduced into the inner core through the aluminum source.
[0044] In some embodiments, the mass percentage of aluminum in the aluminum source to the total mass of the ternary cathode material precursor and the lithium source is N, and N satisfies: 0.03wt%≤N≤0.2wt%, which is conducive to the appropriate introduction of aluminum elements, while not reducing the capacity, improving the structural stability and cycle performance of the ternary cathode material. N can further be 0.05wt%~0.18wt%, and can be 0.03wt%, 0.05wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt% or any value within the range of any two of the above values.
[0045] In some embodiments, the lithium source may include at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium sulfate, and the like.
[0046] In some embodiments, the general formula of the ternary cathode material precursor is Ni x Co y Mn 1-x-y (OH)2, where 0.5≤x≤0.7, 0≤y≤0.1, wherein, as x increases, the primary sintering temperature needs to be gradually reduced to better prepare the core of the single crystal.
[0047] In some embodiments, the ratio of the molar number of lithium in the lithium source to the total molar number of transition metals in the ternary positive electrode material precursor can be (1.02~1.3):1, which is conducive to the full incorporation of lithium ions during the formation of the inner core, promotes the uniform distribution of lithium ions in the inner core, reduces the degree of cation mixing, and improves the electrochemical performance and structural stability of the ternary positive electrode material.
[0048] The method of mixing the ternary cathode material precursor, the lithium source and the aluminum source may include mixing with a high-speed mixer, mixing with a plowshare mixer, mixing with a ribbon mixer, stirring or grinding, etc., which can effectively mix the lithium source with the ternary cathode material precursor and promote the interaction between the two. It is understandable that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the lithium source and the ternary cathode material precursor is acceptable.
[0049] Step S2, mixing the inner core with phosphate and performing secondary sintering to form a coating layer containing phosphate on the surface of the inner core to obtain a ternary positive electrode material.
[0050] Specifically, the obtained aluminum-doped core is mixed evenly with phosphate, and then the mixture is subjected to secondary sintering to form a ternary cathode material doped with aluminum and coated with phosphate. The phosphate on the surface of the core can reduce the direct contact between the core and the electrolyte, effectively reduce side reactions, reduce the dissolution of transition metals in the core, and can also improve the surface chemical stability and promote surface charge transfer, thereby improving the structural stability and cycle performance of the ternary cathode material.
[0051] In some embodiments, the mass percentage of the metal element in the phosphate to the total mass of the ternary cathode material precursor and the lithium source is M, and M satisfies: 0.03wt%≤M≤0.2wt%. Adding phosphate according to the above ratio is conducive to adjusting the phosphate coating amount in the ternary cathode material and balancing the performance improvement of the ternary cathode material and the stability of the coating layer. M can further be 0.05wt%~0.1wt%, and can be 0.03wt%, 0.05wt%, 0.12wt%, 0.15wt%, 0.18wt%, 0.2wt% or any value within the numerical range composed of any two of the above values.
[0052] In some embodiments, the phosphate may include at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate. The above phosphates have good chemical stability and ionic conductivity, and can effectively improve the interface stability, cycle performance, rate performance and stability under high voltage of the ternary positive electrode material. The metal elements therein are also beneficial to improving the structural stability and electrochemical properties of the ternary positive electrode material. For example, niobium has strong oxidation stability, which helps to further improve the thermal stability and voltage stability of the ternary positive electrode material; lithium can improve ionic conductivity, enhance the cycle performance and rate performance of the ternary positive electrode material; aluminum can enhance the structural stability of the ternary positive electrode material and improve high temperature performance; cobalt helps to improve the conductivity and stability of the ternary positive electrode material, while improving high voltage performance.
[0053] In some embodiments, the mixing method can be solid-phase dry mixing, such as high-speed mixer mixing, plow mixer mixing, ribbon mixer mixing, stirring or grinding, etc.; it can also be liquid-phase wet mixing, such as wet grinding or spray coating, etc. Reasonable mixing methods and mixing parameters can further effectively improve the coating effect. Specifically, this embodiment can adopt a solid-phase dry method, using a high-speed mixer to evenly mix and coat the kernel and phosphate. Compared with wet spraying, dry mixing is beneficial to reduce the introduction of solvents and improve the stability of the mixture to achieve better coating effects.
[0054] During the secondary sintering process, the temperature of the secondary sintering is 300°C to 800°C. Within the above temperature range, the uniformity, compactness and bonding strength of the phosphate coating layer with the core can be improved, while the core will not change, so that the core maintains a stable layered structure. The temperature of the secondary sintering can further be 600°C to 800°C, and can be illustratively 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or any value within the range formed by any two of the above values.
[0055] The secondary sintering time can be 6h~18h, which is conducive to sufficient sintering to form the coating layer. The secondary sintering time can further be 12h~16h, and can be exemplarily 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h or any value within the range of any two of the above values.
[0056] In some embodiments, the atmosphere of the secondary sintering can be air atmosphere, oxygen-rich atmosphere or pure oxygen atmosphere, which is conducive to maintaining the oxidation state of the metal ions in the ternary cathode material. The atmosphere of the primary sintering can further be oxygen-rich atmosphere or pure oxygen atmosphere.
[0057] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By mixing the precursor of the ternary positive electrode material with the aluminum source and sintering it once, the bulk doping of the aluminum element is achieved, thereby reducing the degree of cation mixing of the ternary positive electrode material and improving the structural stability of the ternary positive electrode material.
[0058] 2. Using a higher primary sintering temperature is conducive to obtaining a single-crystal ternary positive electrode material, which is convenient for aluminum doping and phosphate coating, and further improves the structural stability and cycle performance of the ternary positive electrode material.
[0059] 3. By coating phosphate, the chemical stability and conductivity of the surface of the ternary positive electrode material are improved, and the interface stability, cycle performance and rate performance of the ternary positive electrode material are improved.
[0060] 4. The preparation method is simple and efficient, which is conducive to the large-scale production of ternary positive electrode materials and has excellent commercial prospects.
[0061] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the positive electrode plate 10 includes a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described above.
[0062] The electrochemical device 100 prepared using the aforementioned ternary positive electrode material has the advantages of high structural stability, high cycle stability and long life, and can be suitable for long-term high-temperature cycle use, meeting the requirements for high specific capacity, high power and long cycle life of the electrochemical device 100.
[0063] The above-mentioned ternary positive electrode material and its preparation method and electrochemical device are further described below through specific examples.
[0064] Example 1 Step 1: Select the ternary cathode material precursor Ni 0.66 Co 0.06 Mn 0.28 (OH)2, add the ternary positive electrode material precursor, lithium hydroxide and aluminum oxide into a high-speed mixer and mix them evenly, wherein the ratio of the molar number of lithium in the lithium source to the total molar number of transition metals in the ternary positive electrode material precursor is 1.04:1, and the mass percentage of aluminum element in aluminum oxide to the total mass of the ternary positive electrode material precursor and lithium hydroxide is 0.1wt%; the evenly mixed mixture is sintered once in a pure oxygen atmosphere at a temperature of 945°C for 15h, and then cooled and crushed to obtain an aluminum-doped core.
[0065] Step 2: Put the core and niobium phosphate into a high-speed mixer and mix them evenly, and the added niobium phosphate is calculated so that the niobium element accounts for 0.1wt% of the core of the ternary positive electrode material; the mixed mixture is secondary sintered in a pure oxygen atmosphere at a temperature of 740°C for 10 hours to obtain a single crystal ternary positive electrode material with aluminum doping and a phosphate coating layer.
[0066] Example 2 The difference from Example 1 is that in step S2, the phosphate is selected as lithium phosphate, and the added lithium phosphate is calculated based on the lithium element accounting for 0.1wt% of the core of the ternary positive electrode material. The other steps are basically the same as Example 1, please refer to Example 1.
[0067] Example 3 The difference from Example 1 is that in step S2, the phosphate is selected as aluminum phosphate, and the aluminum phosphate added is calculated based on the aluminum element accounting for 0.1wt% of the core of the ternary positive electrode material. The other steps are basically the same as Example 1, please refer to Example 1.
[0068] Example 4 The difference from Example 1 is that in step S2, the phosphate is cobalt phosphate, and the added cobalt phosphate is calculated based on the cobalt element accounting for 0.1wt% of the core of the ternary positive electrode material. The other steps are basically the same as Example 1, please refer to Example 1.
[0069] Example 5 The difference from Example 1 is that in step S1, the mass percentage of aluminum element in aluminum oxide to the total mass of the ternary positive electrode material precursor and lithium hydroxide is 0.03wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0070] Example 6 The difference from Example 1 is that in step S1, the mass percentage of aluminum element in aluminum oxide to the total mass of the ternary positive electrode material precursor and lithium hydroxide is 0.2wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0071] Example 7 The difference from Example 1 is that in step S2, the mass percentage of niobium element in the added niobium phosphate to the core is 0.03wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0072] Example 8 The difference from Example 1 is that in step S2, the mass percentage of niobium element in the added niobium phosphate to the core is 0.2wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0073] Comparative Example 1 The difference from Example 1 is that in step S2, no phosphate is added. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0074] Comparative Example 2 The difference from Example 1 is that in step S1, no aluminum source is added. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0075] The following tests were performed on the ternary positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-2.
[0076] Test method: 1. Scanning electron microscope (SEM) test: The ternary positive electrode materials prepared in Example 1 and Comparative Example 1 were observed by scanning electron microscope.
[0077] 2. Electrochemical performance test: Battery preparation: The ternary positive electrode materials, conductive agent SP and mixed liquid NMP prepared in Examples 1-8 and Comparative Examples 1-2 were evenly mixed in a mass ratio of 90:5:5. The speed of slurry pulling was 2000 rpm for 90 min. After coating and cutting, the pieces were vacuum dried at 120°C for 12 h and transferred to a glove box. The metal lithium sheet was used as the negative electrode and the battery shell was CR2032 to make a button battery.
[0078] Performance Test: The LAND battery test system was used for constant current charge and discharge tests. During the test, the working voltage range of the first discharge capacity test was 2.8V~4.4V, the temperature was 25℃, and the current density was 1C to measure the first discharge capacity of the battery. The cycle performance test was carried out at a working voltage range of 2.8V~4.4V, a temperature of 45℃, and 100 cycles at a current density of 1C to measure the capacity retention rate of the battery.
[0079] The relevant test results of Examples 1-8 and Comparative Examples 1-2 are shown in Table 1.
[0080] The above results show: like Figure 3 As shown, the single crystal ternary positive electrode materials doped with aluminum and coated with phosphate in Example 1 are composed of particles with a particle size ranging from 1 μm to 10 μm, have a single crystal morphology, good particle roundness, uniform particle size, and good dispersibility. This is due to the control of the primary sintering temperature and duration in Example 1, thereby forming single crystal particles with a suitable particle size. In addition, the scanning electron microscope image of the ternary positive electrode material in Comparative Example 1 is as follows Figure 4 As shown, by comparing the scanning electron microscope images of Example 1 and Comparative Example 1, it can be found that the surface of the ternary positive electrode material particles in Example 1 is smooth due to the presence of phosphate, while the ternary positive electrode material in Comparative Example 1 is also in a single crystal form, but the surface of the particles is rough and there are some small particles and powders. This shows that the phosphate coating layer is evenly coated on the surface of the particles, making the surface of the particles smoother, the coating effect is good, and the metal dissolution can be effectively improved, thereby improving the storage performance.
[0081] Combining Table 1 and Figure 5It can be seen that the first charge and discharge capacity of the ternary positive electrode materials in Examples 1-8 are all at a relatively high level. Among them, the first charge capacity of the battery made of the ternary positive electrode material in Example 1 reached 222.9mAh / g, while Comparative Example 1 was only 220.6mAh / g, and Comparative Example 2 was only 221.2mAh / g. From the perspective of the first discharge capacity, compared with the first discharge capacity of Comparative Examples 1-2, Examples 1-4 have all been improved. This is because the aluminum doping improves the stable structural properties of the ternary positive electrode materials in Examples 1-4, and at the same time, the phosphate coating improves the surface chemical stability and conductivity of the ternary positive electrode materials. The synergistic effect of the two improves the charge and discharge capacity of the battery prepared with the ternary positive electrode material.
[0082] Combining Table 1 and Figure 6 It can be seen that the ternary positive electrode materials in Examples 1-8 have good layered structures and less side reactions with the electrolyte due to the aluminum doping and phosphate coating, and the cycle stability of the prepared batteries at high temperatures is better than that of Comparative Examples 1-2. After 100 cycles, the capacity retention rate of Examples 1-4 is still at a high level. However, when the cycle of Comparative Example 2 is close to 80 cycles, the capacity retention rate drops sharply. This is attributed to the fact that Comparative Example 2 has no aluminum doping and phosphate coating, and the structural stability is poor. After multiple lithium ion insertion and extraction processes at high temperatures, the structure collapses and the capacity retention rate drops sharply.
[0083] Therefore, in Examples 1-8 of the present application, aluminum is doped into the inner core and phosphate is coated on the surface of the inner core. The two act synergistically to improve the structural stability and cycle performance of the ternary positive electrode material, so that the battery has a good first charge and discharge capacity and can be stably cycled at high temperatures.
[0084] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A ternary positive electrode material, characterized in that: It comprises a core and a coating layer located on the surface of the core, wherein the core is doped with aluminum elements and the coating layer contains phosphate.
2. The ternary positive electrode material according to claim 1, characterized in that: The ternary positive electrode material is a single crystal ternary positive electrode material.
3. The ternary cathode material according to claim 1, characterized in that: The mass percentage of aluminum element in the ternary positive electrode material is A, and A satisfies: 0.03wt%≤A≤0.2wt%.
4. The ternary cathode material according to claim 1, characterized in that: The mass percentage of the metal element in the phosphate to the ternary positive electrode material is B, and B satisfies: 0.03wt%≤B≤0.2wt%.
5. The ternary cathode material according to claim 1, characterized in that: The phosphate includes at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate.
6. A method for preparing a ternary positive electrode material, characterized in that: include: The ternary cathode material precursor, the lithium source and the aluminum source are mixed to form a mixed material, and the mixed material is sintered once to obtain an aluminum-doped core; The inner core is mixed with phosphate and subjected to secondary sintering to form a coating layer containing phosphate on the surface of the inner core, thereby obtaining the ternary positive electrode material.
7. The method for preparing a ternary cathode material according to claim 6, characterized in that: The aluminum source includes at least one of aluminum oxide, aluminum hydroxide, aluminum carbonate, aluminum chloride, aluminum sulfate and aluminum phosphate; and / or The mass percentage of the aluminum element in the aluminum source to the total mass of the ternary positive electrode material precursor and the lithium source is N, and N satisfies: 0.03wt%≤N≤0.2wt%.
8. The method for preparing the ternary cathode material according to claim 6, characterized in that: The mass percentage of the metal element in the phosphate to the core is M, and M satisfies: 0.03wt%≤M≤0.2wt%; and / or The phosphate includes at least one of niobium phosphate, lithium phosphate, aluminum phosphate and cobalt phosphate.
9. The method for preparing a ternary cathode material according to claim 6, characterized in that: The primary sintering temperature is 800°C to 1000°C, and the primary sintering time is 6h to 18h; and / or The temperature of the secondary sintering is 300° C. to 800° C., and the time of the secondary sintering is 6 h to 18 h.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is a ternary positive electrode material as described in any one of claims 1 to 5 or a ternary positive electrode material prepared by the preparation method of a ternary positive electrode material as described in any one of claims 6 to 9.